Violence and violence control in karate: Has there been a sportization process? - van Gestel, J. (International Review for the Sociology of Sport, 2019)
Sport-related violence is a critical issue in the sociology of sport. This paper draws upon Elias`s concept of sportization to examine changes in patterns of violence and violence control in karate in Belgium. By employing a new and unique quantitative approach to the issue of violence, more accurate data has been gathered on the changing patterns of rewards and sanctions associated with different techniques, from full impact (violent) to no-touch (non-violent) techniques. Results show that over several decades, and with the exception of some early developments, sports karate has witnessed a reduction in the value and scoring of violence and, from the 1980s, an increase in the scoring of no-touch and light-impact techniques. This is indicative of a sportization trend, one aspect of which involves the greater control of violence. The results are explained primarily with reference to intensifying and equalizing interdependencies between, on the one hand, the national and regional karate federations and, on the other, governmental institutions and international sports organizations.